2021
DOI: 10.1007/s11356-021-13242-9
|View full text |Cite
|
Sign up to set email alerts
|

Facing metal stress by multiple strategies: morphophysiological responses of cardoon (Cynara cardunculus L.) grown in hydroponics

Abstract: The contamination of environments by heavy metals has become an urgent issue causing undesirable accumulations and severe damages to agricultural crops, especially cadmium and lead which are among the most widespread and dangerous metal pollutants worldwide. The selection of proper species is a crucial step in many plant-based restoration approaches; therefore, the aim of the present work was to check for early morphophysiological responsive traits in three cultivars of Cynara cardunculus (Sardo, Siciliano, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…In particular, Kovácik et al [ 30 ] found that the activation of the enzyme phenylalanine ammonia-lyase (PAL) increases the concentration of phenolic metabolites in Matricaria chamomilla . Decline in plant photosynthesis, as induced by heavy metals stress, is usually combined with stomatal restrictions [ 31 ]. In those circumstances, limiting stomata openings reduces the stream of carbon dioxide entering the leaf cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Kovácik et al [ 30 ] found that the activation of the enzyme phenylalanine ammonia-lyase (PAL) increases the concentration of phenolic metabolites in Matricaria chamomilla . Decline in plant photosynthesis, as induced by heavy metals stress, is usually combined with stomatal restrictions [ 31 ]. In those circumstances, limiting stomata openings reduces the stream of carbon dioxide entering the leaf cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the latter result, we hypothesize that these smaller cells could entrap a higher fraction of metals into their cell walls, which are well known as metal sequestration sites, e.g., [30]. Accordingly, the same cultivar, in the presence of Cd and Pb, developed more numerous and smaller stomata to preserve net photosynthesis efficiency under metalstress [23].…”
Section: Discussionmentioning
confidence: 88%
“…Our results showed that both metals entered the cytoplasm of the three cultivars here examined, but Sardo showed an accumulation of Cd and Pb significantly higher than the other two cultivars, especially in the roots. In a previous work [23], similar intra-cellular metal fractions (i.e., concentrations in EDTA washed leaves) were measured in the same three cardoon cultivars after 30 days of growth. The shorter exposure time chosen here to show genotoxicity [16], could have highlighted a peculiar trait (i.e., a faster metal accumulation capacity) of Sardo during the early growth stages.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The decrease in root elongation induced by photoaging is a result of plant defense against this external stress. It has also been reported [ 28 , 29 ] that the inhibition of cell elongation and local cell division is a common manifestation of stress-induced morphological changes in plants to mitigate toxicity effects. In contrast, pristine MP exposure showed no significant effect on the growth of seedling stems, and only the particles photoaged for 14 d caused the stems to exhibit an increase in elongation.…”
Section: Resultsmentioning
confidence: 99%